Reversible cerebral vasoconstriction syndrome with concurrent bilateral carotid artery dissection. (May 2013) - Bayer-Karpinska, Anna; Patzig, Maximilian; Adamczyk, Christopher; Dimitriadis, Konstantinos; Wollenweber, Frank A; Dichgans, Martin; Jahn, Klaus; Opherk, Christian
Background: The pathophysiological basis of reversible cerebral vasoconstriction syndrome is poorly understood but carotid artery dissection has been discussed as a rare possible cause. So far, only single cases of unilateral carotid artery dissection and reversible cerebral vasoconstriction syndrome have been reported. Case: Here, we describe the case of a 54-year old patient presenting to the emergency department with right hemiparesis, hypaesthesia and dysarthria. Furthermore, he reported two episodes of thunderclap headache after autosexual activity. Cerebral imaging showed ischaemic infarcts, slight cortical subarachnoid haemorrhage, bilateral carotid artery dissection and fluctuating intracranial vessel irregularities, compatible with reversible cerebral vasoconstriction syndrome. An extensive diagnostic work-up was normal. No typical trigger factors of reversible cerebral vasoconstriction syndrome could be found. The patient received intravenous heparin and the calcium channel blocker nimodipine. Follow-up imaging revealed no vessel irregularities, the left internal carotid artery was still occluded. Conclusion: This case supports the assumption that carotid artery dissection should be considered as a potential trigger of reversible cerebral vasoconstriction syndrome, possibly by altering sympathetic vascular tone.